Studies on melt processable biocomposites of polylactic acid - Joseph, Seena; Deenadayalan, E.; Mahanwar, Prakash A. (Journal of Polymers and the Environment, 2015)
Melt processable microcrystalline cellulose (MCC)/poly(lactic acid) (PLA) composites were successfully prepared by twin-screw extrusion. Several characterization techniques were used to investigate the effect of MCC on rheological behavior, morphology, crystallization and melting behavior of the PLA and structure-property correlation of the MCC/PLA composites has been established. Rheological measurements showed that the addition of MCC has a dramatic influence on the low frequency relaxations of PLA chains and above 5 % of MCC, it forms percolated network structure. Differential scanning calorimeter analysis showed that MCC acted as nucleating agent enhancing crystallization below the percolation concentration. Properties of MCC/PLA composites have been compared with that of talc and CaCO3 filled composites. Talc is found to be more effective in crystallizing PLA than MCC and CaCO3. MCC/PLA composites are found be melt processable like that of talc and CaCO3 filled PLA composites.
Keywords: Biopolymers; composites; Rheological properties; Structure-property relationship

Polylactic acid (PLA) biocomposites filled with waste leather buff (WLB) - Ambone, Tushar; Joseph, Seena; Deenadayalan, E.; Mishra, Satyendra; Jaisankar, S.; Saravanan, P. (Journal of Polymers and the Environment, 2017)
A large amount of leather waste is generated from tanning industries and most of which are disposed of landfill or discharged into the natural water bodies without any treatment, causing environmental problems. The aim of this study is to develop eco-biocomposites using waste leather buff (WLB) as filler in Polylactic acid (PLA) matrix to reduce the environmental issues and provide sustainable solution. WLB/PLA composites were prepared by twins-screw micro extruder varying the WLB content from 2% to 30 wt%. These composite were extensively characterise by several techniques. Tensile properties of the composites showed addition of WLB resulted in improvement of tensile property of composite and reduction in percentage crystallinity of PLA matrix observed with increase in WLB content. The effect of WLB on properties of interfacial adhesion and dispersion in WLB/PLA composites were studied by SEM. Wettability of composites was tested by contact angle and water absorption studies. WLB/PLA composite showed increase in water absorption with WLB loading. These WLB/PLA composite could be used to develop low cost eco-friendly product material.

Processing and characterization of waste leather based polycaprolactone biocomposites - Joseph, Seena; Ambone, Tushar S.; Salvekar, Abhijit V.; Jaisankar, S. N.; Saravanan, P.; Deenadayalan, E. (Polymer Composites, 2017)
Waste leather buff (WLB) filled polycaprolactone (PCL) composites were prepared by twin-screw extrusion varying the WLB content from 2% to 40%. These composites were extensively characterized by several techniques in order to establish micro and macroscopic properties. Addition of WLB resulted in improvement of tensile modulus of neat PCL and reduction in percentage crystallinity of PCL matrix was observed with increase in WLB content. Interfacial adhesion and dispersion of WLB on PCL matrix was investigated using Scanning Electron Microscope. Percentage of water uptake increased with increase in concentration of WLB in the composite. These biodegradable composites could be used to develop low cost materials suitable for applications in footwear industry, for making bags, suitcases, etc., eliminating the environmental issues arising from WLB generated from tanneries in leather industry. POLYM. COMPOS., 38:2889-2897, 2017. (c) 2015 Society of Plastics Engineers

Self-assembly of novel Fmoc-cardanol compounds into hydrogels - analysis based on rheological, structural and thermal properties - Kadeeja, Aliya; Joseph, Seena; Abraham, Jancy Nixon (Soft Matter, 2020)
Hydrogels of low molecular weight molecules are particularly appealing for various biomedical applications such as drug delivery, tissue engineering, and antitumor therapy due to their excellent biocompatibility, biodegradability, and easy availability. Fmoc-peptide hydrogels form an essential category of these hydrogels. Herein we report a new class of Fmoc hydrogels in which cardanol (3-pentadecyl phenol (PDP)) is covalently linked with fluorenylmethyloxycarbonyl group. Cardanol is a plant-based renewable raw material, readily obtained from Cashew Nut Shell Liquid (CNSL). The long aliphatic chain of pentadecyl phenol helps in bringing a structural incompatibility and generates different nanostructures such as nanospheres, nanotapes, and nanofibers depending on Fmoc substitution and the solvents used. Stable hydrogels were formed from Fmoc-PDP in DMSO/H2O, and the critical aggregation concentration (CAC) and critical gelation concentration (CGC) were determined. The role of non-covalent forces such as hydrogen-bonding, hydrophobicity, and pi-pi stacking interactions in governing self-assembly to hydrogel formation was studied for Fmoc, DiFmoc and Boc groups attached to PDP. The thermal properties were analyzed, and smectic and nematic phases were identified for the molecules depending on the substitutions involved. Overall the study supports the mechanisms of aggregation and gelation in novel Fmoc-cardanol derivatives.

Injectabledextran-fluorenylmethoxycarbonylphenylalanine composite hydrogels with improved mechanical properties - Abraham, Jancy N.; Joseph, Seena; Trivedi, Rishabh; Karle, Mrunal (Polymer International, 2021)
Low molecular weight hydrogels are recently gaining importance owing to their applications in material sciences and biology. A new class of composite hydrogel was developed using polysaccharides such as dextran and fluorenylmethoxycarbonyl phenylalanine (FmocF) in a phosphate buffer. The molecular weight and concentration of the dextran were varied to obtain rigid but injectable hydrogels without using other crosslinking agents. From the different molecular weights of dextran studied (5k, 40k and 70k), a combination of FmocF (0.6% w/v) and dextran 40k (0.012% w/v) composite gels yielded a maximum value of storage modulus of approximately 1500 Pa, which is 3.5 times higher than the storage modulus of pure FmocF gels. Scanning electron microscopy of FmocF/dextran composite gels revealed highly tangled fibrous structures with dense branches and lower fiber diameter compared to pure FmocF gels. The high-intensity hydrogen-bonded N-H peak in the infrared spectra showed enhanced hydrogen bonding in FmocF/dextran composite gels compared to pure FmocF gels. The dextran acts as an impurity in the process of fibrillation, leading to a crystallographic mismatch, and densely packed thin fibers are formed. These gels exhibited gel to sol and sol to gel conversion with temperature or external stress and showed injectable behavior. (c) 2020 Society of Industrial Chemistry
Keywords: Dextran; Fmoc-Phe; hydrogels; injectable gels; Rheology

Linear poly(lactic acid) ionomers with pendant ionic groups - Joseph, Seena; Menon, Abhijith Hari; Lele, Ashish K.; Chikkali, Samir H. (New Journal of Chemistry, 2024)
Although PLA is widely used, melt processing of this polymer is still a challenging task. In our efforts to improve the melt strength and processability of PLA, we report the synthesis of high molecular weight linear PLA ionomers. PLA copolymers (CP1-CP3) with pendant alkyne groups were synthesized by reacting L-lactide with propargylated lactide. The existence of copolymers with alkyne groups was unambiguously demonstrated, and the percentage of alkyne was found to be 3-7%. A click reaction protocol was developed to treat the resultant alkyne functionalized copolymers (CP1-CP3) with mercaptosuccinic acid (MSA) and pendant carboxylic acid group functionalized copolymers (CP1-MSA1 to CP3-MSA3) were obtained. The 1-2D NMR confirmed the formation of a major MSA bis-addition product, along with a minor mono-addition product. In the final step, the MSA functionalized copolymers were treated with sodium hydride (NaH) to obtain the corresponding linear PLA ionomers (CP1-MSA1-Na1 to CP3-MSA3-Na3). Significant improvement in thermal and melt rheological properties was observed in these ionomers, as compared to the precursor copolymer and unmodified PLA, due to the microstructural changes caused by the association of the ionic groups. Storage modulus (G `) and loss modulus (G `') values showed a substantial increase in melt elasticity of the ionomers with G ` > G `', whereas the unmodified PLA melt behaved like a viscoelastic liquid. Detailed investigation reveals that incorporating pendant ionic groups in a high molecular weight linear PLA remarkably enhances the elastic modulus from 10 to 100 000 Pa (four orders of magnitude).

Renewable and degradable polyoxalates derived from castor oil - Menon, Abhijith Hari; Joseph, Seena; Shaikh, Maulali H.; Chikkali, Samir H. (Macromolecular Chemistry and Physics, 2025)
Renewable feedstocks pave the way to reduce the demand for petroleum-derived chemicals. Castor oil is one such plant-based raw material that can be used to synthesize chemicals and materials with diverse applications. Herein, we report the synthesis of a novel monomer, 18-methoxy-18-oxooctadec-9-en-7-yl methyl oxalate (3), from castor oil-derived ricinoleic acid. The identity of the monomer 3 has been unambiguously ascertained using 1-2D NMR spectroscopic analysis. Monomer 3 was then subjected to condensation polymerization with potentially bio-renewable long-chain aliphatic diols to yield degradable linear polyoxalates having molecular weights in the range of 8000-22,000 g/mol. The polymerization reactions were performed using pTSA and [Sn(Oct)2] as catalysts, and the polymerization conditions were optimized. The structure of the polymer was confirmed by 1-2D NMR spectroscopy, IR spectroscopy, and GPC analysis. The thermal characterizations of the polyoxalates were carried out by DSC and TGA analysis. The polyoxalates were found to degrade in acidic media. These renewable polyoxalates were further reacted with thiols by ``thiol-ene'' click reaction to produce a cross-linked rubbery polymer, which retained degradability.
Keywords: castor oil derivatives; hydrolytic degradations; polyoxalates